Rhipicephalus sanguineus as biological vector of Anaplasma platys in dogs - Forlano, María Dalila (2019)
The aim of this study was to determine the involvement of the tick Rhipicephalus sanguineus in the transmission of Anaplasma platys in canines. A canine was inoculated with a strain of A. platys and once it developed parasitemia confirmed by smears and PCR, it was infested with nymphs and adults of R. sanguineus. The engorged ticks were collected, the intestine and the salivary gland were collected from the ticks fed in the inoculated canine and a PCR was performed. DNA from A. platys was not amplified in the macerated nymphs, in post-molded adults without feeding, or in adults fed from the experimentally inoculated canine. The results indicate that R. sanguineus does not participate in the transmission of A. platys.